A proposal of a conceptual framework for the development of entomology research projects and related sciences - Farji-Brener, Alejandro G. (Revista Colombiana de Entomología, 2019)
Planning research projects is a challenge that many students fail to successfully overcome. A lack of formal training in research planning and design, an excessive emphasis on analysis rather than on ideas and a lack of a guide are some of the possible causes of this problem. This essay proposes a conceptual framework that is of didactic utility to guide students in their research projects in entomology and related sciences. Three approximations and three approaches are presented. The proposed approximations are: descriptive, deductive observational and deductive experimental. The first is useful to design descriptive projects, where natural patterns are discovered and determined, and thus it is unnecessary and inaccurate to specify hypotheses and predictions. Deductive approximations use the hypothetical-deductive method and thus need to specify a priori the ideas being tested and the consequences if they are true. In the first deductive approximation, the predictions come from observational data, while in the second they come from experiments. Three approaches proposed are: comparative, associative and manipulative. The first two approaches can be used in both the descriptive and the deductive observational approximations. However, the manipulative approach is necessary if the experimental approximation is used. All these approximations and approaches have strengths and weaknesses; they are complementary rather than exclusive and are illustrated with an ecological study. It is expected that this conceptual framework may be a didactic and useful tool for teachers and students.